Crystallographic Orientation Determination of Hexagonal Structure Crystals by Laser Ultrasonic Technique. (January 2016) - Li, W; Coulson, J; Marrow, P; Smith, R J; Lainé, S J; Clark, M; Sharples, S D
Abstract: Spatially resolved acoustic spectroscopy (SRAS) is a laser ultrasonic technique that shows qualitative contrast between grains of different orientation, illustrating the sensitivity of acoustic waves to the material structure. The technique has been improved significantly on determining the full orientation of multigrain cubic metals, by comparing the measured surface acoustic wave (SAW) velocity to a pre-calculated model. In this paper we demonstrate the ability of this technique to determine the orientation of hexagonal structure crystals, such as magnesium and titanium based alloys. Because of the isotropy of the SAW velocity on the basal plane (0001) of hexagonal crystals, the slowness surface is shown as a circle. As the plane moves from (0001) towards (112̄0) or towards (101̄0), the slowness surface gradually turns into an oval. These acoustic properties increase the difficulty in orientation determination. The orientation results of a grade 1 commercially pure titanium by SRAS is presented, with comparison with electron backscattered diffraction (EBSD) results. Due to the nature of SAWs on hexagonal structure crystals, only the results of Euler angles 1 and 2 are discussed. The error between SRAS and EBSD is also investigated.